2018
DOI: 10.1111/nph.15377
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of wheat rachis node infection by Fusarium graminearum – decoding deoxynivalenol‐dependent susceptibility

Abstract: Fusarium graminearum is a filamentous ascomycete and the causal agent of Fusarium head blight on wheat that threatens food and feed production worldwide as infection reduces crop yield both quantitatively by interfering with kernel development and qualitatively by poisoning any remaining kernels with mycotoxins. In wheat, F. graminearum infects spikelets and colonizes the entire head by growing through the rachis node at the bottom of each spikelet. Without the mycotoxin deoxynivalenol (DON), the pathogen cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 74 publications
(108 reference statements)
2
53
0
3
Order By: Relevance
“…In particular, z high concentration of strobilurins inhibits the biosynthesis of ethylene (ET) [ 69 ] but improves the production of abscisic acid (ABA) [ 70 ]. It has been demonstrated that ET contributes to FHB resistance during early infection but then promotes the senescence of wheat heads that favors the fungal colonization in the dead tissues of the host [ 71 , 72 ]. On the other hand, the accumulation of ABA quickly induces the stomatal closure, which prevents the pathogen entry into the host tissues [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, z high concentration of strobilurins inhibits the biosynthesis of ethylene (ET) [ 69 ] but improves the production of abscisic acid (ABA) [ 70 ]. It has been demonstrated that ET contributes to FHB resistance during early infection but then promotes the senescence of wheat heads that favors the fungal colonization in the dead tissues of the host [ 71 , 72 ]. On the other hand, the accumulation of ABA quickly induces the stomatal closure, which prevents the pathogen entry into the host tissues [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…DON is the most commonly found toxin in cereals (Placinta et al, 1999). Previous works showed that DON could have a role in fungal spread beyond the initial infection (Bai et al, 2002) by facilitating the spreading of F. graminearum from spikelets into the rachis which might induce the switch from biotrophy to necrotrophy (Bönnighausen et al, 2018). DON is also known to allow the inhibition of host protein synthesis (Walter et al, 2010), and is believed to be an aggressiveness factor rather than a pathogenicity factor (Proctor et al, 1995;Pasquet et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between FHB symptoms and DON accumulation at harvest might be lower when DON accumulation is normalized by fungal biomass (Miedaner, Reinbrecht, & Schilling, 2000;Voss, Bowden, Leslie, & Miedaner, 2010). DON is known to allow fungal spread beyond initial infection (Bai, Desjardins, & Plattner, 2002;Maier et al, 2006) and might even induce the switch from biotrophy to necrotrophy (Bönnighausen, Schauer, Schäfer, & Bormann, 2019). This illustrates that DON is an aggressiveness factor rather than a pathogenicity factor (Proctor, Hohn, & McCormick, 1995).…”
mentioning
confidence: 99%